Caring for Climate Change Through Socialization and Training on Household Waste Management in Eka Jaya Village - Aliza, Loli; Anggraini, Febri Juita; Ramadani, Ilham; Indah, Indah; Saleksi, Riki; Novelia, Yoli (Universitas Serang Raya, 2025)
Climate change is an environmental issue that is getting more and more attention in science and daily life. One of the contributing factors to climate change is waste management, which is not environmentally friendly. In RT 01 Eka Jaya Village, Jambi City, there is still a habit of people throwing and burning garbage carelessly, which causes greenhouse gas emissions such as CO₂, N₂O, NOₓ, NH₃, and other organic carbon compounds. To overcome this problem, the service team from the Environmental Engineering Study Program, University of Jambi, carried out socialization, training, and the provision of facilities to support the sustainable management and processing of household waste. The activity showed a significant increase in community knowledge and behavior towards waste management, as evidenced by the questionnaire results, namely that 99% of residents understood the correct waste management methods. In addition, the community also gained skills in processing glass waste into paving block products, which has the potential to become a business idea and improve the local economy. This activity shows that an educational and participatory approach can effectively change people's behavior towards better and sustainable waste management.